A preliminary study on ochre sources in Southwestern Germany and its potential for ochre provenance during the Upper Paleolithic - Velliky, Elizabeth C. (2020)
The use of mineral pigments, specifically iron-oxide rich mineral pigments called ochre, has been put forward as a key element in the development of symbolic and non-utilitarian behaviors in human evolution. However, the processes of ochre procurement, trade and use are difficult to conceptualize without the identification and characterization of the sources where these materials were acquired. We present the results of geochemical analyses of ochre source samples collected from the Swabian Jura, Black Forest, and other localities in southern and eastern Germany. The goal of this study was to build the groundwork for future investigations on the range of ochre behaviors at archaeological sites in the region. We aimed to determine whether specific ochre outcrops could be differentiated based on their geochemical signatures. Using data from Neutron Activation Analysis (NAA), we were able to determine that the ochre source regions exhibit greater source inter-variability than infra-variability when observed using a range of statistical techniques, therefore satisfying the provenance postulate. Furthermore, the data provide the foundation for a Central European database of ochre sources to allow the comparison of ochres from different regions to archaeological ochres from important nearby and perhaps distant sites.